A comparative study in narrative discourse of Kannada English bilingual normal adults - N, Hema; K C, Shyamala (Journal of All India Institute of Speech and Hearing, 2011)
The linguistic relativity hypothesis suggests that bilinguals may actually have different thought patterns when speaking different languages, this study, which examines the narration told by individuals in two different languages, sheds further light on the validity of the hypothesis. The current study particularly explores how, when telling narratives, bilingual individuals express verbal notions through the use of the tense, aspect, and voice forms available in each of their two languages. Particularly the past tense is often used in oral narratives, specifying the typical series of events taking place in a particular sequence such as going on a trip or journey to a place. This was the target task of the present study. Here 20 normal bilingual adults were the participants and had to narrate in Kannada and English languages separately. These discourse samples were video recorded using digital handycam DCR-DVD 908. The objective was to compare and see the differences in Kannada and English language narrative discourse. The narrative discourse of these participants were subjected for T-unit analysis; the parameters included were number of clauses, number of T-units, number of words per clauses and number of words per T-unit. Thus the participant’s Kannada and English narrative discourse were quantified separately. The statistical results showed significant differences for the parameter number of clauses, number of T-units and number of words per T-unit of Kannada narrative discourse when compared to English narrative discourse. These similarities and differences in their narrative discourse are further discussed in detail.